PELAKSANAAN KEGIATAN EKSTRAKURIKULER GANDANG TAMBUA DI SMP NEGERI 2 PARIAMAN - Winda Marselina; Syeilendra Syeilendra; Harisnal Hadi (FBS Universitas Negeri Padang, 2017)
Abstract This article aims to describe how the extratracular activities conducted in SMP Negeri 2 Pariaman. Extracurricular is an additional activity for students who are held outside the appointed hours of instruction. The type of research used is qualitative research using descriptive method. The object of this research is the process of extracurricular activities of gandang tambua in SMP Negeri 2 Pariaman. The main instrument is the researcher. This study uses several tools in the field data collection such as stationery and photo cameras. For data collection the authors do literature study, observation and interviews. The results showed that the implementation of extracurricular gandang tambua in SMP Negeri 2 Pariaman done by forming a group of each group consisting of 5orang students, where the training process carried out practically in the room and outside the classroom . To explore the ability that the students themselves in playing the gandang tambua musical instrument, the teacher schedules 7 meetings. From 7 times of meetings, teachers more often use demonstration methods in delivering the material. Keywords: Implementation, Extracurricular, Gandang Tambua